Assessment of community maternal care performance of public health midwives of a province in Sri Lanka: a multi-method approach - Gunathunga, W.; Fernando, D.N. (SEAMEO Regional Tropical Medicine and Public Health Network., 2010)
The maternal care performance of public health midwives' (PHM) was reviewed using 4 methods in a province of Sri Lanka. The objectives of this descriptive study were to provide a comprehensive assessment of their work and to determine the use of a multi-method system to assess their performance in terms of self- assessed competency, knowledge, attitudes and performance of domiciliary and field clinic services. There were 301 (87.2%) PHMs with good or moderate level of knowledge in antenatal care with only 165 (47.8%) and 238 (69.8%) in natal and postnatal care, respectively. Total knowledge decreased with increasing age and duration of service. Self-assessed competencies were high but not positively correlated with actual knowledge. Attitudes were found to indicate dissatisfaction with the job and a preference of clinic services at the expense domiciliary care. The results indicated that continuing education and enhancement of career prospects were necessary. The methods used in this study could be adopted with appropriate modification for evaluation of personnel in similar settings.